2015
DOI: 10.1208/s12248-015-9846-1
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Paritaprevir, Ombitasvir, Dasabuvir, Ritonavir, and Ribavirin in Patients with Hepatitis C Virus Genotype 1 Infection: Combined Analysis from 9 Phase 1b/2 Studies

Abstract: Abstract. Direct-acting antiviral agents (DAAs) are established as the standard of care for chronic hepatitis C virus (HCV) infection. One of the newest additions to the HCV arsenal is an oral three-DAA combination therapy (i.e., the 3D regimen) that does not require concomitant use of pegylated interferon. The clinical development program for the 3D regimen has yielded a robust dataset that is inclusive of various dosing schemes and a diverse patient population. Using data from nine phase 1b/2a/ 2b studies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…This analysis showed that ribavirin coadministration did not affect the pharmacokinetics of any of the DAAs in HCV genotype 1-infected subjects, as ribavirin was not identified as a covariate in any of the analyses. Ribavirin values of clearance and volume parameters estimated from the population pharmacokinetic analysis were in close agreement with those reported in the population pharmacokinetic analysis of phase Ib and II studies of the 3D regimen [25] and in the literature [32,33], suggesting that the pharmacokinetics of ribavirin were not altered when coadministered with the 3D regimen. The weight-based ribavirin dosing used in the clinical trials that contributed to the present analysis provided consistent exposures across the various covariates.…”
Section: Figuresupporting
confidence: 85%
“…This analysis showed that ribavirin coadministration did not affect the pharmacokinetics of any of the DAAs in HCV genotype 1-infected subjects, as ribavirin was not identified as a covariate in any of the analyses. Ribavirin values of clearance and volume parameters estimated from the population pharmacokinetic analysis were in close agreement with those reported in the population pharmacokinetic analysis of phase Ib and II studies of the 3D regimen [25] and in the literature [32,33], suggesting that the pharmacokinetics of ribavirin were not altered when coadministered with the 3D regimen. The weight-based ribavirin dosing used in the clinical trials that contributed to the present analysis provided consistent exposures across the various covariates.…”
Section: Figuresupporting
confidence: 85%
“…21 Similarly, paritaprevir and grazoprevir AUC 24 values in Asian subjects were 30% and 50% higher, respectively, compared to those in whites. [22][23][24] Increased exposures in Asian sub-jects may lead to potential adverse events including alanine aminotransferase and total bilirubin elevations. Alanine aminotransferase elevations have been observed in a small proportion (1%) of patients administered currently approved treatment regimens containing the HCV protease inhibitors paritaprevir/ritonavir, grazoprevir, and asunaprevir.…”
Section: Discussionmentioning
confidence: 99%
“…For M1 only, prediction of UGT inhibition was also based on the ratio (R 1 ) of unbound C max to in vitro enzyme K i . Assumptions are as follows: f m of P450 probe substrates is assumed to be 0.99 (represents an upper estimate of the enzyme contribution; Brown et al, 2005), F g of midazolam as a CYP3A probe substrate was assumed to be 0.53 (Simcyp, version 14.1; Certara, Princeton, NJ), and K a values used for each drug were previously reported (Mensing et al, 2016).…”
Section: Predictions Of Cytochrome P450 and Ugt Interactionsmentioning
confidence: 99%